MENGAKTIFKAN KEMBALI MEDSOS DESA DAN MEMPROMOSIKAN PARIWISATA DESA: PROGRAM PENGABDIAN MASYARAKAT DI DESA COMPANG NDEJING, KECAMATAN BORONG, KABUPATEN MANGGARAI TIMUR - Ladopura, Gayatri; Satu, Innosensia E. Isavela Nd; Bello, Maria Florencia Yunita (Merwinspy Publisher, 2025)
This article discusses a community service program implemented in Compang Ndejing Village, Borong District, East Manggarai Regency, with the aim of reactivating social media as a means of tourism promotion. Social media has become an important tool in disseminating information quickly and attractively, especially in introducing local tourism potential. Through mentoring and creating digital content, the community is encouraged to be actively involved in tourism promotion. The results show an increase in social media interaction, community involvement, and a stronger promotional narrative. This activity proves that good social media management can contribute to improving the image of tourist villages and supporting local economic growth. The method of implementing community service includes several important stages, but for a more systematic academic presentation. The stages of implementing community service that can be presented are problem identification, activity planning, implementation of socialization and training, production and distribution of content, and evaluation and monitoring of impact.